PENGARUH MANAJEMEN PERPUSTAKAAN SEKOLAH TERHADAP MINAT BACA PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 INDRALAYA UTARA - Ester Ayunitias; Siti Fatimah; Rusmin AR (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2019)
The title of this research is The influence of school library management on reading interest ofstudents in economic subject at SMA N.1 Nort Indralaya. The purpose of this research is toprove the influence of library management on reading interest of students in economic subjectat SMA N.1 North Indralaya. The population of this research is all of XI IPS class at SMA N.1North Indralaya. For sampling research used Cluster Random Sampling and selected XI IPS 1class with 29 students. The data were collected by questionnaire and observation techniques.The result of this research showed that the school library management included good criteria.This is looking from the observation result of six assessment aspects are library collection, facilities & infrastructures, library services, library worker, and implementation & management. The data analysis used percentage formula with the result 85% with good criteria. Besides that, the data analysis of questionnaire used simple linear regression test obtained Fhitung bigger than Ftabel is 7,16≥4,21so that, Ho rejected and Ha accepted, it’s mean that there is influences in economic subject. The suggestion for library managers should be improve the collect management, library facilities, and human resource management to increase the students interested on reading class, especially for economic subject.